Klasik Tefsir Hareketlerinin Mûsâ-Hızır Kıssası Bağlamında Mukayesesi - Güloğlu, Nazife Vildan (Abant Izzet Baysal Universitesi Ilahiyat Fakultesi Dergisi, 2021)
It can be mentioned that there are three main gloss methods as declaration, comprehension, and evidence in the efforts of Islamic tradition to interpret religion. What are the reflections of the mentioned three main systems in the interpretation tradition? In this article, classical gloss movements specific to Moses and al-Khiḍr parable are aimed to be compared. The relation between the methods that glossators follow and interpretation differences are also aimed to be identified in the same direction. Therefore, how they interpret the verses between 60th-82nd of Sūrat al-Kahf, where the parable is told, is examined. The explanations of prominent glossators of each movement are categorized and comparison method is applied in the meanwhile. The study is expected to contribute to the literature especially in this respect. It is observed that classical interpretations mostly interpret the parable with a theologian and faqīh perspective. For example, even the interpretations about the attributes of the people in the parable are intended to explain rather the activities of al-Khiḍr in the frame of Kalām and Fiqh. Although it is not as many as Declaratory Gloss Method, Comprehensive Gloss Method has also been consulted in some interpretations. As a result, it is observed that Qurʾān passages that have different statement categories or ways of addressing are generally explained according to the method of the glossator.

İslâmî geleneğin dini yorumlama çabaları için beyan, irfan ve burhan olmak üzere üç ana te’vil yönteminden bahsedilebilir. Zikredilen bu üç genel yapının tefsir geleneğindeki yansımaları nasıldır? Bu makalede, Mûsâ-Hızır kıssası özelinde klasik tefsir hareketlerinin mukayese edilmesi hedeflenmiştir. Aynı doğrultuda müfessirlerin takip ettikleri yöntem ile yorum farklılıkları arasındaki ilişkinin tespit edilmesi de amaçlanmıştır. Bunun için de onların, kıssanın anlatıldığı Kehf sûresinin 60-82. âyetlerini nasıl yorumladıkları incelenmiştir. Her bir akımın önde gelen müfessirlerine ait izahlar, kategorize edilmiş ve bu esnada karşılaştırma yöntemi uygulanmıştır. Özellikle bu açıdan çalışmanın literatüre katkı sağlayacağı umulmaktadır. Klasik tefsirlerin ekseriyetle kıssayı bir kelamcı ve fıkıhçı bakış açısıyla yorumladıkları görülmüştür. Mesela kıssada geçen şahısların sıfatları ile ilgili yorumlar dahi daha çok Hızır’ın ortaya koyduğu faaliyetlerin Kelam ve Fıkıh İlmi çerçevesinde izahını mümkün kılmaya yöneliktir. Beyanî te’vil yöntemi kadar çok olmasa da bazı tefsirlerde irfânî te’vil yöntemine de başvurulmuştur. Sonuç olarak farklı ifade kategorisi ya da hitap şekillerine sahip Kur’ân pasajlarının, genellikle müfessirin takip ettiği yönteme göre izah edildiği müşahede edilmiştir.
Keywords: Interpretation; the Parable of Moses and al-Khiḍr; Declaratory Gloss Method; Comprehensive Gloss Method; Sūrat al-Kahf; Tefsir; Mûsâ-Hızır Kıssası; Beyanî Te’vil; İrfânî Te’vil; Kehf Sûresi